Sources, Transformations, Syntheses, and Bioactivities of Monoterpene Pyridine Alkaloids and Cyclopenta[c]pyridine Derivatives - Xuejian Zhang; Feiyan Tao; Tao Cui; Cheng Luo; Zhigang Zhou; Yuchuan Huang; Lanlan Tan; Wei Peng; Chunjie Wu (Molecules, 2022)
Monoterpene pyridine alkaloids (MTPAs) are alkaloids derived from iridoid glycosides (IGs). The common molecular structure of MTPAs is the pyridine ring, while some of them have a cyclopenta[c]pyridine skeleton. Some compounds containing this structure are potentially bioactive medicinal agents. In this paper, seven drug candidates (A–G), ninety natural source products (1–90), thirty-seven synthesized compounds (91–127), as well as twenty-six key intermediates (S1–S26) were summarized. We categorized five types of MTPAs and one type of cyclopenta[c]pyridine alkaloids in all. Additionally, their possible genetic pathways were proposed. Then, the chemical transformation, biotransformation, chemical synthesis, as well as the bioactivity of MTPAs and cyclopenta[c]pyridine derivatives were analyzed and summarized. Cyclopenta[c]pyridine derivatives can be concisely and chirally synthesized, and they have shown potentials with antibacterial, insecticidal, antiviral, anti-inflammatory, and neuropharmacological activities.